2011
DOI: 10.1002/lsm.21097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of photodynamic therapy for lung cancers

Abstract: Our translational research suggests that NPe6-PDT may be superior to Photofrin-PDT for the treatment of lung caner, and individualized approaches to PDT based on the expression status of Bcl-2 and/or BCRP may improve the efficacy of PDT in patients with lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Thus, as in performing PDT with TS, large vessels must be kept shielded from the treatment laser to avoid embolism. In fact, microvasculature damage and its subsequent effect on the vascular system surrounding the tumor was identified as a basis for TS’s antitumor activity when it was first introduced in Japan for treating early stage lung cancer ( 27 ). The fluorescence emission from blood vessels might explain why the area under the ROC curve (0.792) for TS in our study was a bit smaller than that reported for 5-ALA (0.88) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as in performing PDT with TS, large vessels must be kept shielded from the treatment laser to avoid embolism. In fact, microvasculature damage and its subsequent effect on the vascular system surrounding the tumor was identified as a basis for TS’s antitumor activity when it was first introduced in Japan for treating early stage lung cancer ( 27 ). The fluorescence emission from blood vessels might explain why the area under the ROC curve (0.792) for TS in our study was a bit smaller than that reported for 5-ALA (0.88) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenomena reported here will be examined under more pertinent pH and pO 2 conditions. Successful clinical protocols have utilized both NPe6 and BPD 21,22 . The sequential approach proposed here would therefore not involve any new photosensitizing agents of unknown efficacy.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Several preclinical studies and some clinical trials suggest that the use of PDT in combination with established treatments or with newly-developed modalities may be of benefit as compared to the individual modalities [20]. As PDT induces apoptosis, inflammatory reactions, immune reactions, and subsequently damage to the microvasculature around the tumor, interestingly, there is evidence now that the mechanisms responsible for the anticancer effects of various PS upon PDT somewhat differs, as in the example of Photofrin-PDT and NPe6-PDT [21]. Usuda J et al [21] examined the role of immunological reactions in the anti-tumor effects of PDT using cytokine-over-expressing cells and investigated whether the anti-apoptotic protein Bcl-2 may be a molecular target.…”
Section: Introductionmentioning
confidence: 99%
“…As PDT induces apoptosis, inflammatory reactions, immune reactions, and subsequently damage to the microvasculature around the tumor, interestingly, there is evidence now that the mechanisms responsible for the anticancer effects of various PS upon PDT somewhat differs, as in the example of Photofrin-PDT and NPe6-PDT [21]. Usuda J et al [21] examined the role of immunological reactions in the anti-tumor effects of PDT using cytokine-over-expressing cells and investigated whether the anti-apoptotic protein Bcl-2 may be a molecular target. They also investigated the association between ATP-binding cassette transporter protein-breast cancer-resistant protein (BCRP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation